A survey of conservation of sea spider and Drosophila Hox protein activities. (November 2015) - Saadaoui, Mehdi; Litim-Mecheri, Isma; Macchi, Meiggie; Graba, Yacine; Maurel-Zaffran, Corinne
Abstract: Hox proteins have well-established functions in development and evolution, controlling the final morphology of bilaterian animals. The common phylogenetic origin of Hox proteins and the associated evolutionary diversification of protein sequences provide a unique framework to explore the relationship between changes in protein sequence and function. In this study, we aimed at questioning how sequence variation within arthropod Hox proteins influences function. This was achieved by exploring the functional impact of sequence conservation/divergence of the Hox genes, labial, Sex comb reduced, Deformed, Ultrabithorax and abdominalA from two distant arthropods, the sea spider and the well-studied Drosophila . Results highlight a correlation between sequence conservation within the homeodomain and the degree of functional conservation, and identify a novel functional domain in the Labial protein. Highlights: Conservation/divergence of Drosophila and pycnogonid Hox proteins A predominant role of the HD for evolutionary functional conservation Identification of a novel Hox functional motif